Exploring Strengths and Weaknesses of Powtoon as Educational Media for Teaching Young Learners - Juniasih, Ni Nengah (International Journal of Digital Learning on Languages and Arts (IJODLLA), 2025)
The development of technology has been touching all level of education. It was important for the teacher to involve technology in the learning process. The common purpose of utilization technology-based in teaching was to make the students more motivated, interest, and engage in the learning process. The use of educational media closely related with its strengths and the weaknesses. This research was aimed to investigate the strength and the weaknesses of PowToon as one of Educational media in the learning process. This research used descriptive qualitative method. The participants who were involved are 3 teachers from Kindergarten level and Elementary school level in Buleleng regency, Bali Indonesia. The data were collected through observation and interview and data analysis were done after that. The result showed that PowToon was chooses because it is easy to use and can create more that one type of educational media. the use of PowToon motivates the students in achieve the learning objectives and understand better the new concept. While the weaknesses were PowToon needs internet connection and not all teacher were able to use the application. PowToon cannot be used in all material that was given to young learners.